Optimising graft survival in endothelial keratoplasty for endothelial failure secondary to cytomegalovirus endotheliitis - Chew, Milton C. (J Ophthalmic Inflamm Infect, 2019)
BACKGROUND: There is limited information regarding Descemet stripping automated endothelial keratoplasty (DSAEK) for endothelial failure secondary to cytomegalovirus (CMV) endotheliitis. Treatment is difficult with high recurrence rates. We describe a case when systemic valganciclovir therapy is directed by aqueous CMV-DNA levels, leading to good graft survival. FINDINGS: A 59-year-old male with bilateral CMV endotheliitis despite antiviral therapy developed endothelial failure and underwent DSAEK. Prior to surgery, aqueous polymerase chain reaction (PCR) for CMV was repeatedly performed, where CMV-positive episodes were treated with systemic valganciclovir. Monthly aqueous analysis was performed until CMV-DNA was undetectable before DSAEK was performed. Post-operative prophylactic systemic valganciclovir treatment was instituted and switched to topical valganciclovir treatment when aqueous samples were negative for CMV. CONCLUSION: Targeted aqueous sampling for CMV-DNA perioperatively guides antiviral therapy and ensures adequacy of treatment, minimising the duration of systemic valganciclovir therapy to reduce adverse effects of long-term treatment.